ASSESSMENT OF WATER QUALITY BASED ON NITRATE, PHOSPHATE, AND AMMONIA CONCENTRATIONS IN BURUK BAKUL VILLAGE, BENGKALIS, RIAU - Sefni Hendris; Dessy Yoswaty; Irvina Nurrachmi; Nabila Afifah Azuga; Bella Billiant J Ananta Kambaren; Rianti Putri; Ardi Gustri Purbata (Asian Journal of Aquatic Sciences, 2025)
Coastal ecosystems are highly sensitive to nutrient enrichment, particularly from land-based activities and aquaculture effluents, which contribute to water quality degradation. This study evaluated the concentrations of nitrate, ammonia, and phosphate in the coastal waters of Buruk Bakul Village, Bengkalis, Riau Province, Indonesia. Water samples were collected from four representative stations in August 2025: a river estuary, a shrimp pond, a mangrove rehabilitation site, and a natural mangrove forest. The analysis was conducted using spectrophotometric methods in accordance with the Indonesian National Standards (SNI). Results indicated that nitrate concentrations ranged from 0.0822 to 0.1932 mg/L, ammonia from 0.5705 to 1.7338 mg/L, and phosphate from 0.0845 to 0.299 mg/L. All parameters exceeded the seawater quality standards for marine biota established by the Decree of the Minister of Environment No. 51/2004, indicating a significant anthropogenic influence. The river estuary recorded the highest nitrate and phosphate levels, reflecting inputs from land runoff and domestic waste, while ammonia peaked in the shrimp pond due to aquaculture discharge. Nutrient levels in mangrove-associated stations were lower but still above the threshold, indicating that mangrove ecosystems provide some capacity to retain and transform nutrients, although insufficient for full remediation. Elevated nutrient concentrations pose ecological risks, such as eutrophication and algal blooms, which may disrupt biodiversity and fisheries productivity. This study emphasizes the urgency of improving aquaculture waste management, reducing land-derived nutrient loading, and strengthening mangrove conservation and rehabilitation as integrated strategies to sustain coastal ecosystem health in Buruk Bakul and similar regions. These findings provide a baseline for nutrient management and coastal rehabilitation strategies in western Indonesian waters